Determination of the Poor Mustahiq From Maqasid Shariah Jasser Auda Perspective (Study After the Decision of Baznasâ€™s Chairman Number 33 of 2019) - Johari; Pratama, Herdifa (Journal of Southeast Asian Islam and Society, 2022)
Poverty alleviation is one of the highlights of the Baznas movement as a zakat management center in Indonesia. This highlight is realized in the determination of the poor mustahiq carried out by Baznas. This is where it becomes important to have a comprehensive assessment of the determination of the poor mustahiq. This research is a library research using a normative-philosophical approach. The use of the Maqasid Shariah theory of Jasser Auda in this study is used as a philosophical perspective for analyzing the Decision of Baznasâ€™s Chairman Number 33 of 2019. The results indicate that through the Decision of Baznasâ€™s Chairman Number 33 of 2019, the determination of the poor mustahiq is carried out by involving the Integrated Data Social Welfare belonging to the Ministry of Social Affairs as an instrument in the analysis of â€œhad kifayahâ€ by Baznas. This determination is intended to explore the greater benefit in the distribution of zakat. The theoretical perspective of the systems approach from Maqasid Shariah Jasser Auda in analyzing the Decision of the Chairman of Baznas Number 33 of 2019 is the determination of the poor mustahiq to be an element that will always be dynamic and in harmony with the aim of providing more benefits of zakat distribution than before.